ROLʹ PREDANIJA V ŽIZNI CERKVI SOGLASNO V. N. LOSSKOMU = THE ROLE OF TRADITION IN THE THE LIFE OF THE CHURCH ACCORDING TO V.N.LOSSKY - Leiva, Eduard A. Sablon (2020)
Vladimir N. Lossky’s concept of "Tradition" is quite complex and difficult to synthesize. He was more inclined to describe Tradition than define it, under the conviction that the Tradition of the Church could not be fully expressed by any dogmatic definition. Nor could it be expressed by word per se, or even by silence ("dumb" words) - yet one could "touch" it, live in it mystically within the Church. This Tradition, as Lossky contemplated it, is something dynamic, the very life of the Holy Spirit within the Church. The nature of living Tradition is an indescribable mystery that cannot be comprehended rationally as a set of propositions.According to this concept, Scripture may be rightly interpreted only with the assistance of the Holy Spirit and within the Church, i.e. in the light of Tradition. Interpretation of Scripture fully depends upon and should always be consistent with the experience of the Church. Rather than being the propositional content of revelation, this Tradition is a penetrating light by means of which man can perceive the truth. Only by this light can one understand the essence of Church traditions, including Sacred Scripture. Tradition not only led to the final shape of Scripture, but also determined the limitations of its understanding.It may be said that certain of Lossky’s views are valuable to modern Evangelical Christians. Among these is, first of all, the fundamental recognition of God as the only and infallible source of revelation. Also, Lossky emphasized the natural, vital, necessary connection between practicing theology, or studying the Holy Scripture, and a deep spiritual knowledge of God - otherwise, it is not real theology at all. Further, Lossky’s view is instructive in that it throws light on the Church’s inextricable place in the whole matter of knowing God. It is in the Church that a person learns the truth and learns to correctly understand the essence of Scripture. The last thing to note is that Lossky’s theological method in general, and his concept of Tradition in particular, emphasize the greatness, infinity and transcendency of God’s supernal being.
Nastojaščaja statʹja posvjaščena analizu ponjatija «Predanie» v tvorčestve francuzsko-russkogo bogoslova Vladimira Nikolaeviča Losskogo. Osoboe vnimanie udeljaetsja vzgljadam Losskogo na rolʹ i značenie Predanija, ili Tradicii, v žizni Cerkvi. Polučennye rezulʹtaty analiza dajut osnovanie zaključitʹ, čto v ponimanii ėtogo myslitelja Predanie igraet fundamentalʹnuju rolʹ v postiženii čelovekom istiny i tajny Božestvennoj ikonomii. Ono sodejstvuet i delaet vozmožnymi vernuju interpretaciju i vosprijatie Pisanija v tesnoj svjazi s kafoličeskim (sobornym) soznaniem i pamjatʹju Cerkvi. V konce delajutsja vyvody otnositelʹno ėkumeničeskoj aktualʹnosti vzgljadov Losskogo na Predanie i ego rolʹ v Cerkvi dlja evangelʹskogo christianstva, v častnosti obraščaetsja vnimanie na to, čemu evangeliki mogut segodnja naučitʹsja u Losskogo po ėtomu povodu.
Настоящая статья посвящена анализу понятия «Предание» в творчестве французско-русского богослова Владимира Николаевича Лосского. Особое внимание уделяется взглядам Лосского на роль и значение Предания, или Традиции, в жизни Церкви. Полученные результаты анализа дают основание заключить, что в понимании этого мыслителя Предание играет фундаментальную роль в постижении человеком истины и тайны Божественной икономии. Оно содействует и делает возможными верную интерпретацию и восприятие Писания в тесной связи с кафолическим (соборным) сознанием и памятью Церкви. В конце делаются выводы относительно экуменической актуальности взглядов Лосского на Предание и его роль в Церкви для евангельского христианства, в частности обращается внимание на то, чему евангелики могут сегодня научиться у Лосского по этому поводу.
Keywords: Mysticism; the relationship between Tradition and Scripture; the theology of Vladimir N. Lossky; Tradition; bogoslovie V. N. Losskogo; predanie; vzaimootnošenie meždu predaniem i Pisaniem; misticizm